A case of right superior vena cava draining into the left atrial roof. (February 2016) - Yokoyama, Shinya; Kaneda, Kozo; Yoshida, Yuichi; Nagasaka, Shigeo; Nishiwaki, Noboru
We report the multidisciplinary consideration in a case of right superior vena cava draining into the left atrial roof. A 12-year-old boy was diagnosed with a sinus venosus-type atrial septal defect associated with anomalous right upper pulmonary venous return. However, intraoperative inspection showed the right superior vena cava draining into the left atrial roof, associated with anomalous right upper pulmonary venous return. An anatomical radical operation was performed using a modified conventional technique.